Turnaround Strategies for Mature Industrial-Product Business Units - Hambrick, Donald C.; Schecter, Steven M. (Academy of Management Journal, 1983)
A study of short-term turnaround attempts by mature industrial-product business units found that efficiency-oriented moves, but not entrepreneurial initiatives, were associated with successful turnaround. Three common types of successful turnaround ?gestalts? were found: asset/cost surgery, selective product/market pruning, and piecemeal moves.